Students as Surrogates in Behavioral Business Research: Some Comments. - Watson, David J. H. (The Accounting Review, 1974)
Abstract This article presents a comment on the study of behavioral business utilizing students as surrogates in the U.S. The question of the relationship between individual attitudes and individual behavior is far from settled in psychology. It appears to be nondemonstrative, for it seems perfectly possible for the conclusion to be false even if the premises or the statistical results are true, since it seems possible to find some students that would be good surrogates. A valid surrogation is dependent upon certain properties of the object not necessarily the objects in total.